A survey of cultivated bananas in Perak - Ng, Casey (UTAR Agriculture Science Journal, 2015)
The cultivated bananas are maintained by cultivation alone. If a particular variety is no longer cultivated anywhere, it would disappear for good because it cannot propagate itself. Conversely, if a genetic change (mutation) occurs, the new form may be propagated, given a name, and become a new variety.